A kind of building sun-proof heat-insulating coating and preparation method thereof
By using modified silica aerogel and boric acid microparticles of different particle sizes in building sun protection and heat insulation coatings, the problem of poor sun protection effect of existing paints is solved, more efficient solar radiation absorption and reflection is achieved, the thermal insulation performance and durability of the paint are improved, and the energy-saving needs of high-grade green buildings are met.
Patent Information
- Application Number
- CN202410592963.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-13
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-05-13
AI Technical Summary
The sun protection and thermal insulation coatings of existing building are not good enough, which makes it difficult for the heat in the coating to be completely absorbed and converted, and cannot meet the demand for building energy saving in high-grade green buildings.
By providing a building sun protection and heat insulation coating, using modified silica aerogel and boric acid microparticles of different particle sizes, the light reflection and absorption performance of the coating is adjusted, and the sun protection and heat insulation effect of the coating is improved.
It realizes effective absorption and reflection of solar radiation, reduces the temperature in the building, improves the thermal insulation performance and durability of the paint, and meets the energy-saving needs of high-grade green buildings.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building coatings, and in particular to a building sun-proof and heat-insulating coating and a preparation method thereof. Background Art
[0002] At present, various measures are taken for building insulation, which are mainly achieved through roofs, walls, glass, etc. Among the many measures, roofs and walls occupy the vast majority. Most of them are now painted with reflective insulation coatings on their surfaces to reduce the impact of sunlight on the temperature of buildings, while achieving the purpose of lowering the surface temperature of buildings, thereby lowering the indoor temperature and making the indoor temperature reach a relatively comfortable temperature. This is also one of the effective measures for efficient and environmental protection. Reflective insulation coatings are commonly used in the construction field for sun protection and heat insulation in summer. Although the coating has a good effect, its insulation performance still cannot meet the current high-level green building demand for building energy conservation. Building energy consumption accounts for about a quarter of the total energy consumption in the country, ranking first among all industries. Currently, only 3% of the buildings under construction can meet the energy-saving standards, and the hydrophobic groups of silica aerogels are prone to agglomeration during use, resulting in sedimentation and degradation of product performance.
[0003] For example, the Chinese patent, application number 202110682964.9, a building sunscreen and heat-insulating coating and a preparation method thereof, is prepared by mixing water-based acrylic resin, modified silica aerogel, zinc phosphate, organic fluorine epoxy resin and organic silicone resin to obtain a blend, adding the blend into a stirring tank, stirring evenly and filtering, adding boric acid microparticles and inorganic fillers into the SiO2 sol precursor to fill the defects in the nonlinear optical crystal, thereby regulating the infrared radiation performance, and assuming the function of enhancing the infrared radiation performance in the atmospheric window band, adding a dispersant so that the molecular chain of the dispersant can be fully extended in the aqueous solution, and forming a surface adsorption layer of a certain thickness on the surface of the SiO2 aerogel particles to produce a steric hindrance effect, thereby achieving the purpose of promoting the development of high-level green buildings and improving the dispersion stability of the SiO2 aerogel system.
[0004] However, since boric acid microparticles reduce light reflection, the paint's light reflection effect is reduced, and more light is absorbed and converted. The sun protection effect is not good enough, and the absorption and conversion efficiency is not enough, and a large amount of heat is still difficult to absorb. Summary of the invention
[0005] The embodiment of the present application provides a building sun-proof and heat-insulating coating and a preparation method thereof, thereby solving the problem in the prior art that the sun-proof effect is not good enough, resulting in the difficulty in completely absorbing and converting the heat in the coating, thereby achieving the effect of reflecting solar radiation and reducing the amount of radiation entering the building sun-proof and heat-insulating coating B.
[0006] The embodiments of the present application provide a building sun-proof and heat-insulating coating, including a building sun-proof and heat-insulating coating A and a building sun-proof and heat-insulating coating B.
[0007] Furthermore, the building sunscreen and heat-insulating coating A and the building sunscreen and heat-insulating coating B are mixed before being applied, and the mass ratio of the mixed building sunscreen and heat-insulating coating A and the building sunscreen and heat-insulating coating B is 1-2:4, or the building sunscreen and heat-insulating coating B is applied first, and after drying, the building sunscreen and heat-insulating coating A is applied, and the application thickness ratio of the building sunscreen and heat-insulating coating B and the building sunscreen and heat-insulating coating A is 4:1.
[0008] A method for preparing a building sun-proof and heat-insulating coating, the specific preparation method comprising:
[0009] S1. preparing a silica aerogel, wherein the silica aerogel includes a silica aerogel A and a silica aerogel B;
[0010] S2: mixing water-based acrylic resin, modified silica aerogel A or silica aerogel B, zinc phosphate, organic fluorine epoxy resin and organic silicone resin to obtain a blend;
[0011] S3: adding the blended material into a stirring tank, stirring evenly, filtering, and then adding the blended material into a ball mill for grinding to obtain a ground crude product;
[0012] S4: adding mica powder, aluminum tripolyphosphate and a dispersant to the ground crude product for further fine processing, and high-speed ball milling until the system is uniform to obtain the building sunscreen and heat insulation coating;
[0013] Among them, the raw materials of building sunscreen and heat-insulating coating A are water-based acrylic resin, modified silica aerogel A, zinc phosphate, organic fluorine epoxy resin and silicone resin, and the raw materials of building sunscreen and heat-insulating coating B are water-based acrylic resin, modified silica aerogel B, zinc phosphate, organic fluorine epoxy resin and silicone resin;
[0014] Further, the preparation process of modified silica aerogel A and silica aerogel B is as follows:
[0015] S21: Al(NO3)3 is dissolved in an ethanol solution, Y(NO3)3 and tributyl borate are added, and the mixture is heated under reflux at 90-100°C in a water bath for 4-5 hours to form a clear sol, and the sol is further heated in a constant temperature water bath at 80-90°C for 5-6 hours, and dried, aged, dried and heat-treated to obtain a dry gel powder, which is then pulverized by air flow to obtain boric acid microparticles;
[0016] The dosage ratio of Al(NO3)3 to ethanol solution is 1g:9-10mL; the molar ratio of Y(NO3)3, tributyl borate and Al(NO3)3 is 1:5-6:1.1;
[0017] S22: adding water glass to deionized water to obtain a dilution, passing the dilution through an exchange column filled with acidic styrene cation exchange resin, adding sodium hydroxide solution to adjust the pH value to 5-6, adding boric acid microparticles and inorganic fillers, stirring for 1-2 hours, pouring the obtained sol into a polyethylene mold and letting it stand for 1-2 hours, covering the surface of the initial wet gel with a layer of ionized water, and aging at room temperature for 5-6 hours to obtain wet gel A or wet gel B;
[0018] The dosage ratio of water glass to deionized water is 1 g: 13 mL, the mass fraction of sodium hydroxide is 40%, and the inorganic filler is one or more of calcium chloride, aluminum chloride, and zirconium oxychloride mixed in any proportion;
[0019] S23: placing the obtained wet gel A and wet gel B in a container filled with ethanol for soaking for 2-3 days, drying and heat treating to obtain dry gel powder A and dry gel powder B, and then air flow pulverizing to obtain the modified silica aerogel A and modified silica aerogel B;
[0020] The wet gel A is dried and heat-treated to obtain dry gel powder A, which is then airflow-pulverized to obtain modified silica aerogel A. The wet gel B is dried and heat-treated to obtain dry gel powder B, which is then airflow-pulverized to obtain modified silica aerogel B.
[0021] Furthermore, the dosage ratio of boric acid microparticles to inorganic fillers is 1-4g:1.5g; the dosage ratio of boric acid microparticles to inorganic fillers in wet gel A is 1-2g:1.5g, and the dosage ratio of boric acid microparticles to inorganic fillers in wet gel B is 2-4g:1.5g.
[0022] Furthermore, the preparation process of the dispersant is as follows:
[0023] S41: Under magnetic stirring, acrylic acid, cinnamic acid and deionized water are added to a three-necked round-bottom flask with a reflux condenser, and heated to 60-70°C in a constant temperature water bath, and nitrogen is introduced for protection. An initiator ammonium persulfate aqueous solution is added to the reaction flask, and the reaction is carried out for 2-3 hours to obtain intermediate A;
[0024] The usage ratio of acrylic acid to deionized water is 7.26 g:41 mL, the usage ratio of the initiator ammonium persulfate aqueous solution to acrylic acid is 5 mL:7.26 g, and the molar ratio of acrylic acid to cinnamic acid is 1:1.
[0025] S42: Add glycidyl methacrylate to a three-necked round-bottom flask with a reflux condenser, add deionized water, and reflux at 80-90° C. for 9-10 hours to obtain a clear aqueous solution, which is freeze-dried to obtain a white solid, namely, monomer 2,3-dihydroxymethacrylate;
[0026] The dosage ratio of glycidyl methacrylate to deionized water is 0.99 g:10 mL;
[0027] S43: adding the monomer 2,3-dihydroxymethylacrylate to the intermediate A, heating the mixture to 60-70° C. in a constant temperature water bath, introducing nitrogen for protection, adding an initiator ammonium persulfate aqueous solution to the reaction flask, reacting for 3-4 hours, and obtaining the dispersant;
[0028] The usage ratio of the initiator ammonium persulfate aqueous solution to the monomer 2,3-dihydroxymethylacrylate is 1.6 g:0.886 g, and the molar ratio of the monomer 2,3-dihydroxymethylacrylate to the intermediate A is 1:10.
[0029] Furthermore, in the boric acid microparticles A, the molar ratio of Y(NO3)3, tributyl borate and Al(NO3)3 is 1:3-4:1.1; in the boric acid microparticles B, the molar ratio of Y(NO3)3, tributyl borate and Al(NO3)3 is 1:6-9:1.1.
[0030] Further, boric acid microparticles B are used in the preparation of architectural sunscreen and heat-insulating coating A; boric acid microparticles A are used in the preparation of architectural sunscreen and heat-insulating coating B;
[0031] Among them, the particle size of boric acid microparticles A is 3-6 μm, and the particle size of boric acid microparticles B is 8-15 μm.
[0032] Furthermore, the building sunscreen and heat-insulating coating B also includes boric acid microparticles C, in which the molar ratio of Y(NO3)3, tributyl borate and Al(NO3)3 is 1:0.5-1:1.1; the obtained boric acid microparticles C have a particle size of 0.6-1 μm;
[0033] In the building sunscreen and heat-insulating coating B, the mass ratio of boric acid microparticles C to boric acid particles A is 2-5:1.
[0034] Further, S41: under magnetic stirring, acrylic acid, cinnamic acid and deionized water are added to a three-necked round-bottom flask with a reflux condenser, and heated to 60-70° C. in a constant temperature water bath, nitrogen is introduced for protection, and an initiator ammonium persulfate aqueous solution is added to the reaction flask, and the reaction is carried out for 2-3 hours to obtain intermediate A;
[0035] The usage ratio of acrylic acid to deionized water is 3.63 g:41 mL, the usage ratio of the initiator ammonium persulfate aqueous solution to acrylic acid is 5 mL:3.63 g, and the molar ratio of acrylic acid to cinnamic acid is 1:1.
[0036] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages:
[0037] First, apply the building sunscreen and heat-insulating coating B first, which contains modified silica aerogel B with more boric acid microparticles, which enhances the adhesion to the substrate and the durability of the coating; a higher content of boric acid microparticles will occupy part of the space, increase the porosity of the aerogel, and provide more paths for solar radiation to enter, and the increase of boric acid microparticles also increases the amount of activated ions of light transitions, so that the solar radiation is consumed faster, and the solar radiation on the building sunscreen and heat-insulating coating B is quickly absorbed, and then apply the building sunscreen and heat-insulating coating A, which contains less boric acid microparticles in the modified silica aerogel A, and focuses more on providing sun protection and durability. Moreover, due to the low content of boric acid microparticles, the ability to absorb solar radiation is reduced, and more is reflected out, reducing the amount of radiation entering the building sunscreen and heat-insulating coating B.
[0038] Secondly, by changing the particle radius during preparation, the prepared boric acid microparticles B have a larger radius and can more effectively reflect sunlight, reduce the absorption of light, and thus reduce the surface temperature of the coating; the prepared boric acid microparticles A have a smaller radius. Boric acid microparticles with a smaller particle radius can provide a larger specific surface area, increase the number of light reflections on the particle surface, and increase the consumption rate of solar radiation. Boric acid microparticles with a smaller particle size can be more densely stacked to form more tiny air layers. These air layers can serve as thermal resistance, slow down the transfer of heat, and improve the thermal insulation performance of the coating.
[0039] Third, boric acid microparticles C with a particle size of micrometers are added to the building sunscreen and heat-insulating paint B. When the particle size of the boric acid microparticles is equivalent to or smaller than the wavelength of visible light, light scattering will occur, dispersing the light radiation in all directions, thereby avoiding local concentration of energy on the paint surface and reducing the temperature of the paint and the building surface; through the combination of boric acid microparticles with different particle sizes, the energy is dispersed by the boric acid microparticles C and converted through the boric acid particles A, which greatly improves the conversion capacity of light radiation.
[0040] Fourthly, by increasing the proportion of initiator and reducing the proportion of acrylic acid and cinnamic acid, the molecular chain length of the dispersant is reduced. Although the dispersing ability of silica aerosol is reduced, reducing the molecular chain length of the dispersant allows the boric acid microparticles C to be adsorbed by the larger boric acid particles A. When light is irradiated to the coating surface, the boric acid microparticles C will effectively scatter light radiation due to their nanometer particle size. When the boric acid microparticles C are adsorbed by the boric acid particles A, these scattered light radiations will reach the boric acid particles A in a more dispersed manner. The enhanced effect of light scattering has a huge improvement in the energy conversion efficiency of the boric acid particles A. Since more light radiation is scattered on the boric acid particles A, it can absorb and convert more heat energy, thereby improving its energy conversion effect. DETAILED DESCRIPTION
[0041] In order to facilitate the understanding of the present invention, the present application will be described in more detail below; preferred embodiments of the present invention are given herein, but the present invention can be implemented in many different forms and is not limited to the embodiments described herein; on the contrary, the purpose of providing these embodiments is to enable a more thorough and comprehensive understanding of the disclosed content of the present invention.
[0042] It should be noted that the terms “vertical”, “horizontal”, “up”, “down”, “left”, “right” and similar expressions used in this document are only for illustrative purposes and do not represent the only implementation method.
[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more related listed items.
[0044] Embodiment 1: A building sun-proof and heat-insulating coating, wherein the building sun-proof and heat-insulating coating comprises a building sun-proof and heat-insulating coating A and a building sun-proof and heat-insulating coating B, and the specific preparation steps include:
[0045] S1. preparing a silica aerogel, wherein the silica aerogel includes a silica aerogel A and a silica aerogel B;
[0046] S2: mixing water-based acrylic resin, modified silica aerogel A or silica aerogel B, zinc phosphate, organic fluorine epoxy resin and organic silicone resin to obtain a blend;
[0047] S3: adding the blended material into a stirring tank, stirring evenly, filtering, and then adding the blended material into a ball mill for grinding to obtain a ground crude product;
[0048] S4: adding mica powder, aluminum tripolyphosphate and a dispersant to the ground crude product for further fine processing, and high-speed ball milling until the system is uniform to obtain the building sunscreen and heat insulation coating;
[0049] Among them, the raw materials of building sunscreen and heat-insulating coating A are water-based acrylic resin, modified silica aerogel A, zinc phosphate, organic fluorine epoxy resin and silicone resin, and the raw materials of building sunscreen and heat-insulating coating B are water-based acrylic resin, modified silica aerogel B, zinc phosphate, organic fluorine epoxy resin and silicone resin;
[0050] The preparation process of modified silica aerogel A and silica aerogel B is as follows:
[0051] S21: Al(NO3)3 is dissolved in an ethanol solution, Y(NO3)3 and tributyl borate are added, and the mixture is heated under reflux at 90-100°C in a water bath for 4-5 hours to form a clear sol, and the sol is further heated in a constant temperature water bath at 80-90°C for 5-6 hours, and dried, aged, dried and heat-treated to obtain a dry gel powder, which is then pulverized by air flow to obtain boric acid microparticles;
[0052] The dosage ratio of Al(NO3)3 to ethanol solution is 1g:9-10mL; the molar ratio of Y(NO3)3, tributyl borate and Al(NO3)3 is 1:5-6:1.1;
[0053] S22: adding water glass to deionized water to obtain a dilution, passing the dilution through an exchange column filled with acidic styrene cation exchange resin, adding sodium hydroxide solution to adjust the pH value to 5-6, adding boric acid microparticles and inorganic fillers, stirring for 1-2 hours, pouring the obtained sol into a polyethylene mold and letting it stand for 1-2 hours, covering the surface of the initial wet gel with a layer of ionized water, and aging at room temperature for 5-6 hours to obtain a wet gel;
[0054] The dosage ratio of water glass to deionized water is 1 g: 13 mL, the mass fraction of sodium hydroxide is 40%, and the inorganic filler is one or more of calcium chloride, aluminum chloride, and zirconium oxychloride mixed in any proportion;
[0055] The dosage ratio of boric acid microparticles to inorganic filler is 1-4g:1.5g;
[0056] When the ratio of boric acid microparticles to inorganic fillers is 1-2g:1.5g, wet gel A is obtained; when the ratio of boric acid microparticles to inorganic fillers is 2-4g:1.5g, wet gel B is obtained;
[0057] S23: placing the obtained wet gel A and wet gel B in a container filled with ethanol for soaking for 2-3 days, drying and heat treating to obtain dry gel powder A and dry gel powder B, and then air flow pulverizing to obtain the modified silica aerogel A and modified silica aerogel B;
[0058] The wet gel A is dried and heat-treated to obtain dry gel powder A, which is then airflow-pulverized to obtain modified silica aerogel A; the wet gel B is dried and heat-treated to obtain dry gel powder B, which is then airflow-pulverized to obtain modified silica aerogel B;
[0059] The preparation process of the dispersant is as follows:
[0060] S41: Under magnetic stirring, acrylic acid, cinnamic acid and deionized water are added to a three-necked round-bottom flask with a reflux condenser, and heated to 60-70°C in a constant temperature water bath, and nitrogen is introduced for protection. An initiator ammonium persulfate aqueous solution is added to the reaction flask, and the reaction is carried out for 2-3 hours to obtain intermediate A;
[0061] The usage ratio of acrylic acid to deionized water is 7.26 g:41 mL, the usage ratio of the initiator ammonium persulfate aqueous solution to acrylic acid is 5 mL:7.26 g, and the molar ratio of acrylic acid to cinnamic acid is 1:1.
[0062] S42: Add glycidyl methacrylate to a three-necked round-bottom flask with a reflux condenser, add deionized water, and reflux at 80-90° C. for 9-10 hours to obtain a clear aqueous solution, which is freeze-dried to obtain a white solid, namely, monomer 2,3-dihydroxymethacrylate;
[0063] The dosage ratio of glycidyl methacrylate to deionized water is 0.99 g:10 mL;
[0064] S43: adding the monomer 2,3-dihydroxymethylacrylate to the intermediate A, heating the mixture to 60-70° C. in a constant temperature water bath, introducing nitrogen for protection, adding an initiator ammonium persulfate aqueous solution to the reaction flask, reacting for 3-4 hours, and obtaining the dispersant;
[0065] The usage ratio of the initiator ammonium persulfate aqueous solution to the monomer 2,3-dihydroxymethylacrylate is 1.6 g:0.886 g, and the molar ratio of the monomer 2,3-dihydroxymethylacrylate to the intermediate A is 1:10.
[0066] When using, the building sunscreen and heat-insulating coating A and the building sunscreen and heat-insulating coating B can be mixed before applying, or they can be used in layers by applying the building sunscreen and heat-insulating coating B first, and then applying the building sunscreen and heat-insulating coating A after drying. When used in layers, the application thickness ratio of the building sunscreen and heat-insulating coating B and the building sunscreen and heat-insulating coating A is 4:1.
[0067] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0068] First, apply the building sunscreen and heat-insulating coating B, which contains modified silica aerogel B with more boric acid microparticles, which enhances the adhesion to the substrate and the durability of the coating; the higher content of boric acid microparticles will occupy part of the space, increase the porosity of the aerogel, and allow more paths for solar radiation to enter, and the increase of boric acid microparticles also increases the amount of activated ions of light transition, so that the solar radiation is consumed faster, so that the solar radiation on the building sunscreen and heat-insulating coating B is quickly absorbed, and then apply the building sunscreen and heat-insulating coating A, which contains less boric acid microparticles in the modified silica aerogel A, and focuses more on providing sun protection and durability. Due to the low content of boric acid microparticles, the solar radiation absorption capacity is reduced, and more is reflected out, reducing the amount of radiation entering the building sunscreen and heat-insulating coating B. The low content of boric acid microparticles makes it have better leveling and workability, and can be easily applied on the surface of the building to form a uniform and beautiful coating;
[0069] Mixing architectural sunscreen and heat-insulating coatings A and B can combine the sunscreen and heat-insulating advantages of both. Mixed application can also reduce construction steps, improve construction efficiency, and ensure close bonding between coatings. Mixed coatings can better adapt to various environmental conditions.
[0070] Embodiment 2: The above embodiment obtains a coating with both high sun protection and high heat insulation effects through building sun protection and heat insulation coating B and building sun protection and heat insulation coating A, which is further improved to increase the consumption conversion speed of thermal radiation.
[0071] The preparation process of modified silica aerogel A and silica aerogel B is as follows:
[0072] S21: Al(NO3)3 is dissolved in an ethanol solution, Y(NO3)3 and tributyl borate are added, and the mixture is heated under reflux at 90-100°C in a water bath for 4-5 hours to form a clear sol, and the sol is further heated in a constant temperature water bath at 80-90°C for 5-6 hours, and dried, aged, dried and heat-treated to obtain a dry gel powder, which is then pulverized by air flow to obtain boric acid microparticles;
[0073] The dosage ratio of Al(NO3)3 to ethanol solution is 1g:9-10mL; the molar ratio of Y(NO3)3, tributyl borate and Al(NO3)3 is 1:3-9:1.1;
[0074] When the molar ratio of Y(NO3)3, tributyl borate and Al(NO3)3 is 1:3-4:1.1, boric acid microparticles A are obtained; when the molar ratio of Y(NO3)3, tributyl borate and Al(NO3)3 is 1:6-9:1.1, boric acid microparticles B are obtained;
[0075] Boric acid microparticles B are used when preparing a building sunscreen and heat-insulating coating A; Boric acid microparticles A are used when preparing a building sunscreen and heat-insulating coating B; wherein the particle size of the boric acid microparticles A is 3-6 μm, and the particle size of the boric acid microparticles B is 8-15 μm;
[0076] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0077] By changing the particle radius during preparation, the prepared boric acid microparticles B have a larger radius and can more effectively reflect sunlight, reduce light absorption, and thus reduce the surface temperature of the coating;
[0078] The prepared boric acid microparticles A have a smaller radius. Boric acid microparticles with a smaller particle radius can provide a larger specific surface area, increase the number of light reflections on the particle surface, and increase the consumption rate of solar radiation. Boric acid microparticles with smaller particle sizes can be more densely packed to form more tiny air layers. These air layers can serve as thermal resistance, slow down heat transfer, and improve the thermal insulation performance of the coating. Boric acid microparticles with smaller particle sizes also have better dispersibility and stability, and can be more evenly dispersed in the coating to avoid agglomeration and sedimentation.
[0079] Example 3: Example 2 is further improved by changing the particle size of the boric acid microparticles to optimize the light reflection ability and improve the conversion of thermal radiation to improve the heat conversion ability.
[0080] The building sunscreen and heat-insulating coating B also includes boric acid microparticles C, in which the molar ratio of Y(NO3)3, tributyl borate and Al(NO3)3 is 1:0.5-1:1.1; the obtained boric acid microparticles C have a particle size of 0.6-1 μm;
[0081] In the building sunscreen and heat insulation coating B, the mass ratio of boric acid microparticles C to boric acid particles A is 2-5:1;
[0082] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0083] Boric acid microparticles C with a particle size of micrometers are added to the building sunscreen and heat-insulating paint B. When the particle size of the boric acid microparticles is equivalent to or smaller than the wavelength of visible light, light scattering will occur, dispersing the light radiation in all directions, thereby avoiding local concentration of energy on the paint surface and reducing the temperature of the paint and the building surface; through the combination of boric acid microparticles with different particle sizes, the energy is dispersed by the boric acid microparticles C and converted through the boric acid particles A, greatly improving the conversion capacity of light radiation; scattering can also reduce glare and dazzling light, reducing light pollution.
[0084] Example 4: Example 3 greatly improves the light radiation conversion capacity by adding boric acid microparticles C with a particle size of micrometers into the building sunscreen and heat-insulating coating B. In order to improve its durability, further improvements are made.
[0085] S41: Under magnetic stirring, acrylic acid, cinnamic acid and deionized water are added to a three-necked round-bottom flask with a reflux condenser, and heated to 60-70°C in a constant temperature water bath, and nitrogen is introduced for protection. An initiator ammonium persulfate aqueous solution is added to the reaction flask, and the reaction is carried out for 2-3 hours to obtain intermediate A;
[0086] The usage ratio of acrylic acid to deionized water is 3.63 g:41 mL, the usage ratio of the initiator ammonium persulfate aqueous solution to acrylic acid is 5 mL:3.63 g, and the molar ratio of acrylic acid to cinnamic acid is 1:1.
[0087] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0088] By increasing the proportion of initiator and reducing the proportion of acrylic acid and cinnamic acid to reduce the molecular chain length of the dispersant, although the dispersing ability of silica aerosol is reduced, reducing the molecular chain length of the dispersant allows the boric acid microparticles C to be adsorbed by the larger boric acid particles A. When light is irradiated onto the coating surface, the boric acid microparticles C will effectively scatter light radiation due to their nanometer particle size. When the boric acid microparticles C are adsorbed by the boric acid particles A, the scattered light radiation will reach the boric acid particles A in a more dispersed manner. The enhanced effect of light scattering has a huge improvement in the energy conversion efficiency of the boric acid particles A. Since more light radiation is scattered onto the boric acid particles A, it can absorb and convert more heat energy, thereby improving its energy conversion effect.
[0089] Comparative example: This comparative example uses the building sunscreen and heat insulation coating of Chinese patent application number 202110682964.9;
[0090] The building sunscreen and heat-insulating coatings of Examples 1-3 and the comparative example were tested according to the test standard of JGJ / T287-2014 "Energy-saving Test Standard for Building Reflective Heat-Insulating Coatings", and the test results are shown in the following table:
[0091] Reflectivity(%) Hemispherical reflectivity (%) <![CDATA[Thermal conductivity (W / cm 2 ·K)]]> Embodiment 1 92.2 91.9 0.16 Embodiment 2 92.5 92.1 0.14 Embodiment 3 94.3 93.6 0.08 Comparative Example 89.9 89.1 0.17
[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A building sunscreen and heat-insulating coating, characterized in that it comprises a building sunscreen and heat-insulating coating A and a building sunscreen and heat-insulating coating B; the building sunscreen and heat-insulating coating A and the building sunscreen and heat-insulating coating B are mixed and then applied, and the mass ratio of the building sunscreen and heat-insulating coating A to the building sunscreen and heat-insulating coating B is 1-2:4; or the building sunscreen and heat-insulating coating B is applied first, and after drying, the building sunscreen and heat-insulating coating A is applied, and the coating thickness ratio of the building sunscreen and heat-insulating coating B to the building sunscreen and heat-insulating coating A is 4:1; The specific preparation method of the above-mentioned building sunscreen and heat-insulating coating A comprises: S1. preparing a silica aerogel, wherein the silica aerogel includes a modified silica aerogel A; S2: mixing water-based acrylic resin, modified silica aerogel A, zinc phosphate, organic fluorine epoxy resin and organic silicone resin to obtain a blend; S3: adding the blended material into a stirring tank, stirring evenly, filtering, and then adding the blended material into a ball mill for grinding to obtain a ground crude product; S4: adding mica powder, aluminum tripolyphosphate and a dispersant to the ground crude product for further fine processing, and high-speed ball milling until the system is uniform to obtain the building sunscreen and heat insulation coating A; The preparation method of the above-mentioned building sunscreen and heat-insulating coating B is the same as the preparation method of the building sunscreen and heat-insulating coating A, and specifically comprises: S1. preparing a silica aerogel, wherein the silica aerogel includes a modified silica aerogel B; S2: mixing water-based acrylic resin, modified silica aerogel B, zinc phosphate, organic fluorine epoxy resin and organic silicone resin to obtain a blend; S3: adding the blended material into a stirring tank, stirring evenly, filtering, and then adding the blended material into a ball mill for grinding to obtain a ground crude product; S4: adding mica powder, aluminum tripolyphosphate and a dispersant to the ground crude product for further fine processing, and high-speed ball milling until the system is uniform to obtain the building sunscreen and heat insulation coating B; The preparation process of modified silica aerogel A and modified silica aerogel B is as follows: S21: Al(NO3)3 is dissolved in an ethanol solution, Y(NO3)3 and tributyl borate are added, and the mixture is heated under reflux at 90-100°C in a water bath for 4-5 hours to form a clear sol, and the sol is further heated in a constant temperature water bath at 80-90°C for 5-6 hours, and dried, aged, dried and heat-treated to obtain a dry gel powder, which is then pulverized by air flow to obtain boric acid microparticles; The dosage ratio of Al(NO3)3 to ethanol solution is 1g:9-10mL; when the molar ratio of Y(NO3)3, tributyl borate and Al(NO3)3 is 1:3-4:1.1, boric acid microparticles A are obtained; when the molar ratio of Y(NO3)3, tributyl borate and Al(NO3)3 is 1:6-9:1.1, boric acid microparticles B are obtained, the particle size of boric acid microparticles A is 3-6μm, and the particle size of boric acid microparticles B is 8-15μm; S22: adding water glass to deionized water to obtain a dilution, passing the dilution through an exchange column filled with acidic styrene cation exchange resin, adding sodium hydroxide solution to adjust the pH value to 5-6, adding boric acid microparticles and inorganic fillers, stirring for 1-2 hours, pouring the obtained sol into a polyethylene mold and letting it stand for 1-2 hours, covering the surface of the initial wet gel with a layer of ionized water, and aging at room temperature for 5-6 hours to obtain a wet gel; The dosage ratio of water glass to deionized water is 1 g:13 mL, the mass fraction of the sodium hydroxide solution is 40%, and the inorganic filler is one or more of calcium chloride, aluminum chloride, and zirconium oxychloride mixed in any proportion; the wet gel is divided into wet gel A and wet gel B; the dosage ratio of boric acid microparticles B to the inorganic filler in the wet gel A prepared from boric acid microparticles B is 1-2 g: 1.5g, the ratio of boric acid microparticles A to inorganic filler in the wet gel B prepared from boric acid microparticles A is 2-4g:1.5g; S23: The obtained wet gel A and wet gel B are respectively placed in a container filled with ethanol and soaked for 2-3 days, and dried and heat-treated to obtain dry gel powder A and dry gel powder B, respectively, and then air flow pulverized to obtain the modified silica aerogel A and modified silica aerogel B, respectively.
2. A building sunscreen and heat-insulating coating as claimed in claim 1, characterized in that: The preparation process of the dispersant is as follows: S41: Under magnetic stirring, acrylic acid, cinnamic acid and deionized water are added to a three-necked round-bottom flask with a reflux condenser, and heated to 60-70°C in a constant temperature water bath, and nitrogen is introduced for protection. An initiator ammonium persulfate aqueous solution is added to the reaction flask, and the reaction is carried out for 2-3 hours to obtain intermediate A; The usage ratio of acrylic acid to deionized water is 7.26 g:41 mL, the usage ratio of the initiator ammonium persulfate aqueous solution to acrylic acid is 5 mL:7.26 g, and the molar ratio of acrylic acid to cinnamic acid is 1:1; S42: Add glycidyl methacrylate to a three-necked round-bottom flask with a reflux condenser, add deionized water, and reflux at 80-90° C. for 9-10 hours to obtain a clear aqueous solution, which is freeze-dried to obtain a white solid, namely, monomer 2,3-dihydroxymethacrylate; The dosage ratio of glycidyl methacrylate to deionized water is 0.99 g:10 mL; S43: adding the monomer 2,3-dihydroxymethylacrylate to the intermediate A, heating the mixture to 60-70° C. in a constant temperature water bath, introducing nitrogen for protection, adding an initiator ammonium persulfate aqueous solution to the reaction flask, reacting for 3-4 hours, and obtaining the dispersant; The usage ratio of the initiator ammonium persulfate aqueous solution to the monomer 2,3-dihydroxymethylacrylate is 1.6 g:0.886 g, and the molar ratio of the monomer 2,3-dihydroxymethylacrylate to the intermediate A is 1:
10.
3. A building sunscreen and heat-insulating coating as claimed in claim 1, characterized in that: The building sunscreen and heat-insulating coating B also includes boric acid microparticles C, in which the molar ratio of Y(NO3)3, tributyl borate and Al(NO3)3 is 1:0.5-1:1.1; the obtained boric acid microparticles C have a particle size of 0.6-1 μm; In the building sunscreen and heat-insulating coating B, the mass ratio of the boric acid microparticles C to the boric acid particles A is 2-5:
1.
4. A building sunscreen and heat-insulating coating as claimed in claim 2, characterized in that: In step S41, the usage ratio of acrylic acid to deionized water is 3.63 g:41 mL, the usage ratio of the initiator ammonium persulfate aqueous solution to acrylic acid is 5 mL:3.63 g, and the molar ratio of acrylic acid to cinnamic acid is 1:1.
Citation Information
Patent Citations
A building sun-proof and heat-insulating coating and its preparation method
CN113372776B
Water-based thermal-insulation paint for cement encaustic tiles and roofs and preparation method thereof
CN102352160A
Reflective thermal insulation coating and production process thereof
CN111748253A
Building sunscreen heat insulation coating and preparation method thereof
CN113372776A